Improving The Students’ Speaking Ability Through Conversation Circles For The First Year Students Of Junior High School - Ismayanti; Fikni, Zahratul; Masyuroh, Siti; Marzuki, Muhammad Junaidi (Journal of Authentic Research, 2025)
This study aims to examine the effectiveness of using Conversation Circles in improving the speaking skills of first-year junior high school students at MTs Al-Ihsan NWDI Gelondong. This research used a one-group pretest-posttest pre-experimental design. To collect the data, the researcher conducted a pre-test, provided treatment using the Conversation Circles method, and then conducted a post-test. The participants included 25 students selected as the research sample. Data were analyzed using descriptive statistics and a paired sample t-test. The results revealed a significant improvement in students’ speaking abilities after the implementation of the Conversation Circles method. The average score increased from 61.24 on the pre-test to 74.28 on the post-test, with a gain of 13.04 points. In addition, the standard deviation decreased from 4.01 to 3.73, indicating more consistent improvement across students. The paired samples t-test showed a significance value of p < 0.05, confirming that the method had a statistically significant positive effect on students’ speaking performance.These findings suggest that Conversation Circles can be an effective alternative strategy for EFL teachers to create a more interactive and low-anxiety speaking classroom. The method supports fluency development, builds students’ confidence, and encourages active participation in speaking activities.